Evaluation of the Mechanical Properties of Porous Thermoplastic Polyurethane Obtained by 3D Printing for Protective Gear - Hyojeong Lee; Ran-i Eom; Yejin Lee (Advances in Materials Science and Engineering)
Three-dimensional (3D) printing is an efficient and sustainable technology useful in various manufacturing fields. The aim of this study was to investigate the applicability of thermoplastic polyurethane (TPU) as a 3D printing material and the conditions related to the use of TPU as personal protective equipment. The tensile strength, shock absorption, and compressibility were evaluated for different infill and thickness conditions. An increase in the infill rate led to an increase in the tensile strength, regardless of the sample thickness. Similarly, the compression energy increased as the infill increased. Both the shock absorption and compression properties increased as the thickness decreased under identical infill conditions. The actual shock absorption test data were compared to the results of structural analyses, which confirmed the potential for predicting impact deformation through the analysis of the tensile characteristics and the basic properties of a 3D printed material.